2021
DOI: 10.12688/hrbopenres.13341.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on opioid agonist treatment in Ireland: Protocol for an interrupted time series analysis

Abstract: While opioid agonist treatment (OAT) is the most effective treatment for opioid dependence, it is heavily dependent on regular face-to-face healthcare delivery placing both clients and treatment providers at risk of COVID-19. Following the emergence of COVID-19, policies were rapidly changed in Ireland, with the introduction of national contingency guidelines by the HSE National Social Inclusion Office, beginning in March 2020 to ensure rapid and uninterrupted access to OAT while balancing efforts to mitigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The restructuring of OAT provision, which allowed for increases in take‐away dosing and electronic scripts for pharmacists, was a positive outcome for participants in our study, as has been highlighted in international studies [25]. Prior research has demonstrated multiple benefits of sustained OAT prescription for improving quality of life and in reducing hepatitis C incidence, criminal behaviour [26–28], and overdose risk [29], highlighting the imperative for continuing uninterrupted OAT provision.…”
Section: Discussionmentioning
confidence: 57%
“…The restructuring of OAT provision, which allowed for increases in take‐away dosing and electronic scripts for pharmacists, was a positive outcome for participants in our study, as has been highlighted in international studies [25]. Prior research has demonstrated multiple benefits of sustained OAT prescription for improving quality of life and in reducing hepatitis C incidence, criminal behaviour [26–28], and overdose risk [29], highlighting the imperative for continuing uninterrupted OAT provision.…”
Section: Discussionmentioning
confidence: 57%
“…This study is reported according to the STROBE Standardized Reporting Guidelines for Cross-Sectional Studies (Vandenbroucke et al, 2007). The study protocol is available on HRB Open (Cousins et al, 2021).…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The study observed rates of dropout, accounting for the number of people in treatment on the last day of the previous month, to detect any variation to outcome (C). While we originally planned to assess the impact of changes introduced to the delivery of OAT on number of people on waiting lists and waiting time (Cousins et al, 2021), the required data were not available.…”
Section: Primary Outcomesmentioning
confidence: 99%